Analisis Faktor Pendapatan Asli Daerah (Pad) Kota di Provinsi Jawa Tengah Tahun 2010-2015 - Amadhea T, Chikara (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The main objective of this study is to evaluate and examine the factors that influence Local Original Income (PAD) in six cities in Central Java Province. In this study, the independent variables analyzed include the inflation rate, government spending, and population. Meanwhile, the variable that is used as the main focus or dependent variable is PAD. The data used is secondary data obtained from the official publication of the Central Statistics Agency (BPS), covering the time period from 2010 to 2015. This study involved six cities as objects of analysis, namely Semarang City, Surakarta, Magelang, Salatiga, Pekalongan, and Tegal. To analyze the relationship between variables, the panel data regression method was used which was run with the help of EViews version 9 software. The results of the analysis showed that the population variable had a positive and significant effect on increasing PAD. The same thing was also found in the government spending variable, which was proven to provide a positive and significant contribution to PAD growth. Conversely, the inflation variable showed a negative and insignificant effect on PAD in the six cities during the study period.